Pemilu Legislatif 2004 di Aceh: Antara Intimidasi, Partisipasi dan Mobilisasi Politik - Nurhasim, Moch (Jurnal Penelitian Politik, 2004)
The 2004 legislative election in Aceh descrihing a very fundamental change of political constellation. The powetful o fth e Islamic basis party is an astonished phenomenon in the political constellation of Aceh based on the 2004 legislative election results. However, the victory of Golkar party which is in balanced with PPP (Partai Persatuan Pembangunan) must be underlined that this New Order party in Aceh is also powetful. Eventhough there are fundamental political changes, we stillfind an intimidation, terror, and political mobilisation in the 2004 legislative election. It happened because of this election was carried out in military emergency situation.